Nilai Heroisme dalam Narasi Digital: Analisis Semiotika Roland Barthes pada Video 'Unseen Heroes' oleh Telkom Indonesia - Setiawan, Joe Harrianto; Salsabila Meidiana Putri (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2025)
Heroism reflects values such as empathy, sacrifice, love, and courage, which positively impact communities. Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, contributing IDR 8,573.89 trillion to the GDP and employing 97% of the workforce, can be regarded as unsung heroes due to their significant role in enhancing societal welfare. Digitalization is a crucial element in empowering MSMEs, with a reported 30% increase in income for those adopting digital platforms. This study analyzes the YouTube video "Unseen Heroes: Srikandi Penerus Tradisi," which tells the story of Ni Made Rini Wahyuni, a Balinese MSME entrepreneur. Using Roland Barthes' semiotics, the study explores heroism values through the concepts of denotation, connotation, and myth. The findings reveal that Ni Made’s journey exemplifies heroism in preserving traditions while leveraging modern technology. The video portrays MSMEs as everyday heroes playing a vital role in social and economic transformation.